Prevalence and Severity of Sleep Bruxism in Edentulous Patients - Naiara Luchi Klöppel; Patrícia Pauletto; Naiany Meiriely de Almeida Lopes; Franciele Floriani; Rangel Lidani; Graziela De Luca Canto; Analucia Gebler Philippi; Luis André Mezzomo (Wiley, 2024)
Conclusions: Almost 8 out of 10 edentulous patients have SB. Approximately half of the SB-detected patients showed moderate to severe severity of bruxism as measured by a commercial, at-home device.